Molecular and Immunological Identifications of Giardia Sp. Isolated From Humans, Dogs and Rodents - Ngah Zasmy Unyah (2004)
Concentrations and staining methods for identification of Giardia parasites in faecal materials from humans and animals are still the routine methods of diagnosis of giardiasis. Introduction of new and sensitive immunological and molecular methods will definitely facilitate diagnosis and the identification of various Giardia species that will ultimately improve clinical management and control of disease transmission. The identification of specific proteins of Giardia parasites, which are genus and species specific, may further improve the specificity and sensitivity of diagnostic methods. In this study, identification and confirmation of the species of Giardia parasite found in Malaysia, particularly in humans, dogs and rodents were done by Polymerase Chain Reaction (PCR) using species-specific primers. Specific Heat-Shock Protein (HSP) as markers for species identification were done using Sodium Dodecyl Sulphate-Polyacrylamide Gel Electrophoresis (SDS-PAGE) and Western Immunoblotting (WI). These markers were used as antigens for the production of species-specific monoclonal antibodies (MAb). The objectives of this study were: i) to identify the common Giardia sp. infecting humans and other mammals (dogs and rodents) in Malaysia using specific Giardia primers by PCR; ii) to produce in vitro and detect immunogenic HSP using polyclonal sera from rabbit immunised with antigens from known Giardia species on WI, and iii) to produce species-specific MAb from the identified HSP markers. Microscopically, this study has observed that G. intestinalis (GI) and G. duodenalis (GD) were indistinguishable but G. muris (GM) can be distinguished from GI or GD. In addition, this study has also confirmed that PCR using species-specific primers was more reliable and accurate in detecting the variant of GI found in humans and dogs. GD isolates recovered from dogs was found to be the actual variant of GI of humans. Clear morphological differentiations and identifications of GM and GI based on microscopical examination were observed and similar results were obtained by PCR using species-specific primers of respective species of Giardia. However, the SDSPAGE and WI failed to identify species-specific HSP markers, but WI using immunised rabbit sera detected four immunogenic HSP, with the molecular weight of 30 kDa, 34 kDa, 58 kDa and 66 kDa. These four immunogenic HSP were detected at 25°C, 37 °c and 50°C in both GI and GM. Three species-specific MAbs were produced using the combinations of the four immunogenic HSPs as antigens. These MAbs were designated as (i) [32 kDa HSPMAbGi(IgG3)], (ii) [29 kDa HSPMAbGm(IgM)], and (iii) [20 kDa HSPMAbGi(IgGl)]. [32 kDa HSPMAbGi(IgG3)] MAb was specific for GI variant found in humans, [29 kDa HSPMAbGm(IgM)] MAb was specific for GM and [20 kDa HSPMAbGi(IgGl)] was specific for GI variant in both humans and dogs. These findings suggest that GI is the main causative agent of giardiasis in both humans and urban dogs in Malaysia GM is the main Giardia parasite infecting rodents in both rural and urban areas in Malaysia.